Design of a Triboelectric Charge Measurement System - Madan, Francesca (My University, 2023)
Tribo-charging is the scientific phenomenon of particles collecting charge through frictional collisions. Disadvantages of tribocharging can occur during powder-handling operations, for instance particle deposition and adhesion. In more extreme cases when particles are excessively charged, electrostatic discharge may occur and cause fire or explosion hazards. With its negatives there are positives, as tribocharging is used in many industries such as the automotive, pharmaceutical, and waste management, coal, and food industry. Research would be beneficial in understanding how the powders perform in operational settings, such as the blending and separation processes. The chemical and physical properties play a key role in affecting the manufacture process and final product. Understanding the chemical or physical composition of the different particles can result in a more effective process. Methods for collecting this charge are a Faraday cup, on-line current measurement, Electric Low-Pressure Impactor (ELPI), and Electronic Single Particle Relaxation Time (ESPART). Research articles have predominately been completed with measurement research using the Faraday cup. Factors that can affect the charging are humidity, work function, particle size, and particle morphology. This project aims to analyze the physical and chemical composition of food-grade powders by creating a system that will transport particles consistently and reliably through a tube to have the charge created by tribo-charging accurately measured. Once the charge is collected, external factors affecting the charge are to be compared and analyzed based off the ratio or compositional make-up of the powder. The goal can be achieved by creating an offline charge measurement system and pairing it with a consistent mass delivery system. Meaning the mass and charge are measured at the beginning and end of the process, not in real-time. Two mass delivery and one charge measurement systems for online measurement were designed and constructed, and one design for both mass delivery and charge measurement for an offline system were designed and constructed. Online measurement means that real-time data for the charge and mass are being collected to obtain the charge-mass ratio at that exact time frame. The mass delivery designs are as followed: • 1st Design: Screw feeder and vibrator hybrid to create consistent flow rate and no “clumping” of materials. However, the design proved to have fluctuations within the mass, and the contact of the Faraday cup with the exit tubing caused the powder delivery to have extra forces that skewed the mass measurements. • 2nd Design: A fluidized bed was utilized in tandem with vibrator, however external and internal factors like mass of powder, air flow resistance, and location of powder within the bed caused a flowrate that was able to increase, but not at a consistent rate. The first charge measurement system was planned to be an online charge measurement using an electrometer and the Faraday cup as a verification method for results. However, the charge measured did not match the mass in relation to time. This could have been due to charged particles escaping the Faraday cup and coating the charged tube – essentially grounding it and stopping any further measurements from being completed. In addition, incorrect grounding of the system caused the charge to flow towards any unground section of the system. This caused no charge measurement and the danger of having a charge lingering on the system. Finally, electrical issues were caused by the loose charged powder that escaped the Faraday cup and came into contact with any of the electrical equipment within range. The offline charge measurement is comprised solely of the Faraday cup connected to an electrometer. The third mass delivery offline design, utilizing the fluidized bed, is being implemented and the offline charge measurement system is also in use. Each section of the charge measurement and mass delivery is contained to prevent further electrical damage of equipment. Trail runs for comparison of dried/undried pure powders, mixture ratio of combination powders, airflow, sifted particle size, and protein content have been completed to analyze the effect these factors have on the charge-mass ratio of the powders. Looking at the experiments, it can be seen that dried pure powders have a higher charge-mass ratio than undried pure powders. Further the sifted size ranges show smaller particle sizes obtain greater charge-mass ratios. While the powder mixtures should show directly proportional charge-mass ratios to the ratio of powders mixed it, this is not the case due to total mass accumulated at the end of the system. However, protein content testing resulted in showing accurate representation of the ratios mixed for each powder. Therefore, hypothesis for the non-linear relationship could be due to the aggregation or coagulation of the two pure powders. Airflow was analyzed from 5-20 LPM and the mass-charge ratio was collected, the results showed an increase in overall mass-charge ratio, but at both 10 and 20 LPM there were “drops” or decrease in charge. The reason for the charge-mass ratio increase can be attributed to the impact force and the decrease in charge-mass ratio can be attributed to the laminar or turbulent phase of airflow. Finally, protein content results indicated that as the wt% increases, the charge-mass ratio also increased, with the exception of chickpea flour. It was hypothesized that both particle shape and size played key roles in effecting the charge-mass ratio of chickpea flour, using SEM photos both size distribution of the particles and shape of particles were analyzed. Results indicated that the particle size was within the range, but the shape of the chickpea flour was spherical which can cause better fluidization. Therefore, it was determined that the shape or morphology of the particles played a more influential role in changing the charge-mass ratio of the particle, causing it to be an outlier. Mathematical modelling, using Matsuda’s tribocharging model based on repeated particle impacts on the wall was used to determine the effect of the work function for the particles. It was concluded that the charge-mass ratio and contact potential difference increased in proportion to each other. This trend was also seen with the protein content of each powder and the contact potential difference. Analysis for the math modelling corresponded with the results in the real time experiments. Observing that the results were already anticipated, no new conclusions could be drawn from the math modeling. Further research should be conducted to determine effects of humidity and acidity/basicity on tribo-charging and how it can be correlated with protein content results or other environmental factors. Specifically with acidity and basicity, tests to determine functional groups would need to be completed and the results correlated with charge and compared against other external factors such as protein content. In addition, for the math modeling, calculations to find the exact values for the mean collision numbers could lead to more accurate contact potential difference or work function values for the effect of particle charge.